2018
DOI: 10.1016/j.juro.2018.01.046
|View full text |Cite
|
Sign up to set email alerts
|

Detrusor Acontractility after Acute Spinal Cord Injury—Myth or Reality?

Abstract: In contrast to the common notion of an acontractile detrusor during acute spinal cord injury, almost two-thirds of our patients showed unfavorable urodynamic parameters within the first 40 days after spinal cord injury. Considering that early treatment of neurogenic lower urinary tract dysfunction in patients with acute spinal cord injury might improve the long-term urological outcome, urodynamic investigation should be performed timely to optimize patient tailored therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 29 publications
2
24
0
Order By: Relevance
“…3 -40 days after SCI) 36,37 . Early treatment to avoid higher intravesical pressure with lower bladder compliance followed by vesicoureteral reflux associated with DO has been suggested to keep patients' renal and bladder function serving as a 'low pressure tank' without waiting for the irreversible complications of SCI 36,37 .…”
Section: Loss Of Pdgfrα + Cells Caused By Sci Were Due To Apoptotic Changes In Detrusormentioning
confidence: 99%
“…3 -40 days after SCI) 36,37 . Early treatment to avoid higher intravesical pressure with lower bladder compliance followed by vesicoureteral reflux associated with DO has been suggested to keep patients' renal and bladder function serving as a 'low pressure tank' without waiting for the irreversible complications of SCI 36,37 .…”
Section: Loss Of Pdgfrα + Cells Caused By Sci Were Due To Apoptotic Changes In Detrusormentioning
confidence: 99%
“…10,11 However, Bywater et al demonstrated that a significant portion of early SCI patients had abnormal urodynamic parameters before 40 days post injury, and they advocated earlier targeted therapies to preserve upper and lower urinary tract function. 12 Children may experience a shorter duration of spinal shock as compared to adults, causing some experts to allow for evaluation earlier than 3 months. 11 Balancing against that recommendation, an early assessment may demonstrate poor parameters before bladder function has fully recovered, thus necessitating repeat invasive testing.…”
Section: Evaluation Of Neurogenic Bladdermentioning
confidence: 99%
“…Urodynamic evaluation is the cornerstone in the evaluation of lower urinary tract dysfunction in SCI patients, but its technique and timing are essential [6,12,14] . Several urological authorities and guidelines recommend performing the first study 3 to 6 months after the injury [8,12,14] , as recent evidence has shown that adverse urodynamic parameters can appear as early as 40 days after SCI [15] . However, in our practice, the first UDS is performed at the first sign of change in the urinary tract.…”
Section: Urodynamic Studymentioning
confidence: 99%